A Hij?? as Cognitive–Ethical Theater: A Pedagogical Case Study of Al-Mutanabb? : Pedagogical Applications - Darwish, Layla (International Journal of Language and Literary Studies, 2026)
This paper reconceives al-Mutanabb?’s Hij?’ as a form of cognitive ethical theater, where conflicts of identity, power, and value are enacted through carefully crafted linguistic performance. Hij?’ operates via cognitive mechanisms such as foregrounding, ostensive communication, and metarepresentational reasoning, guiding audience attention and structuring moral evaluation. The study also proposes a pedagogical framework in which students analyze linguistic and performative cues, reconstruct social hierarchies, and reflect on ethical inversions, cultivating critical thinking and literary sensitivity. In this perspective, classical Arabic satire is revealed not merely as a historical genre but as a dynamic practice of reasoning, judgment, and interpretive engagement.